2017
DOI: 10.1097/qai.0000000000001296
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: Pharmacokinetics of Crushed Elvitegravir Combination Tablet Given With or Without Enteral Nutrition

Abstract: We investigated whether a fixed-dose combination tablet of elvitegravir, cobicistat, emtricitabine, and tenofovirDF (Stribild) can be crushed and combined with enteral nutrition without influencing pharmacokinetics. This was an open-label, 3-period, single-dose, randomized, crossover trial in 24 healthy volunteers. Subjects received Stribild whole tablet with breakfast (reference), crushed/suspended Stribild + breakfast, crushed/suspended Stribild + enteral nutrition. Crushed/suspended Stribild + enteral nutri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…The SODF size and shape, generic availability, oral powder or solution availability, alteration of SODF, and food considerations of the commonly used ARV drugs are summarized in Table I [12, [19][20][21][22][23][24][25][26], Table II [12, 27,28], and Table III [8,12,[29][30][31][32][33].…”
Section: Arv Medicationsmentioning
confidence: 99%
“…The SODF size and shape, generic availability, oral powder or solution availability, alteration of SODF, and food considerations of the commonly used ARV drugs are summarized in Table I [12, [19][20][21][22][23][24][25][26], Table II [12, 27,28], and Table III [8,12,[29][30][31][32][33].…”
Section: Arv Medicationsmentioning
confidence: 99%
“…In an open label, crossover study of 24 healthy adults, the crushed combination tablet demonstrated bioequivalence (80%-125%) in regard to area under the curve (AUC) and C max when administered with enteral nutrition feeds. 90 One case report even found a sustained virologic response to the crushed combination tablet over a 4-week period. 91 In contrast, compounding a liquid formulation from the single tablet regimen of tenofovir disopoxil fumarate, emtricitabine, and efavirenz did not meet bioequivalent standards in regard to AUC and C max of efavirenz and tenofovir and the investigators recommended against crushing the combination tablet.…”
Section: Drug Delivery/drug–drug Interactionsmentioning
confidence: 99%
“…14 Crushing elvitegravir containing combination tablets have previously been described with similar AUC and C max compared to normal oral administration. 90 In one study of 80 HIV patients both with and without dysphagia, chewing raltegravir tablets resulted in significantly higher drug absorption and had less interpatient pharmacokinetic variability compared to swallowing tablets whole ( P = .004). 94 In regards to crushing dolutegravir tablets, two case reports have recently been published.…”
Section: Drug Delivery/drug–drug Interactionsmentioning
confidence: 99%
“…Consequently, reduced drug bioavailability, especially for drugs such as rilpivirine (RPV) with complex absorption patterns, may lead to subtherapeutic concentrations, potential viral rebound and drug resistance development 1–8 . Unfortunately, there is a lack of data comparing the administration of crushed and whole tablet formulations of ART drugs 8–11 . RPV is a non‐nucleoside reverse transcriptase inhibitor with a relatively low genetic barrier to resistance compared to protease inhibitors or second‐generation integrase inhibitors, resulting in a higher risk of resistant variants in case of virological failure.…”
Section: Introductionmentioning
confidence: 99%